An exploratory survey of on-site heat stress management practices in the Canadian mining industry. - Tetzlaff, Emily J.; O'Connor, Fergus K.; Meade, Robert D.; Kenny, Glen P. (Journal of Occupational & Environmental Hygiene)
With climate change fueling more frequent and intense periods of hot weather, heat stress management programs are becoming increasingly important for protecting the health and safety of workers in the Canadian mining industry. While the inclusion of heat-mitigation measures such as those provided by the American College of Governmental Industrial Hygienists (ACGIH) Threshold Limit Values (TLVs) are commonly employed by industry, there is a need to develop more comprehensive industry-specific measures for heat stress prevention and management. To better understand current heat management practices and identify opportunities for improvement, an exploratory survey of 51 employees responsible for health and safety at underground mining (n = 35), and surface operations (n = 16) (e.g., open-pit mining, milling, smelting, and exploration site) was conducted in Canada. The respondents answered 50 questions related to workplace heat stress management, including descriptors of the workplace environment, perceived heat stress hazard, administration of heat stress management programming, heat stress emergency procedures, environmental monitoring strategies, and knowledge of mining-specific regulations related to heat stress. Twenty-four managers (47%) reported that heat-related illnesses led to restricted duty or lost time claims at their site, with a median of 5 [IQR: 2–10, max: 30] reportable heat-related illnesses occurring per site annually. Many also felt that heat-related illnesses are under-reported by their workforce (n = 36, 71%). Most sites reported established heat stress management programs to prevent heat illness (n = 43, 84%), typically based on the TLVs (n = 38, 75%). Although some organizations do conduct pre-task evaluations for heat stress (n = 30, 59%), more than half do not conduct post-job evaluations (n = 28, 55%) or pre-employment screening for heat stress vulnerability (n = 3, 6%). While our findings indicate that the health and safety managers recognize the hazard posed by heat and have stated practices to help address the hazard, we also observed inconsistencies in heat stress management programming across the sample. Developing and adopting a standard heat stress management and reporting system would be an important step toward protecting workers from existing and emerging threats from extreme heat and climate change.